Preparation of coal-based low-dimension carbon materials and the applications in organic solar cells - Yong ZHAO; Min LIU; Jianlei QUE; Peng HUANG (Meitan kexue jishu)
Coal, as an abundant carbon resource, holds a crucial position in the energy industry. However, conventional coal utilization methods are linked to environmental pollution and inefficiency. At the molecular level, coal and its derivatives display properties of polycyclic aromatic hydrocarbons, which could be transformed into valuable low-dimensional carbon materials (0D, 1D, and 2D) through physical and chemical processes. This transformation plays a significant role in achieving cleaner coal utilization and promoting the development of renewable energy sources. The article first elaborates on the current situation of energy and environment in China, as well as the urgent need for clean utilization of coal resources in the “dual carbon” era. The structural features, preparation methodologies, modification strategies, and new energy applications of coal-derived low-dimensional carbon materials, including carbon quantum dots, carbon nanotubes, graphene, carbon nanosheets, and etc. are explored. Additionally, it elucidates the benefits and limitations, innovation, as well as suitable conditions of various preparation techniques of low-dimensional carbon materials. Furthermore, it investigates the diverse applications of these materials in the components of organic solar cells (OSC), highlighting their application superiority and mechanisms as electrodes, additives, and charge transport layers in detail. The pivotal role of coal-based low-dimensional carbon materials in enhancing the power conversion efficiency of OSC, reducing manufacturing costs, improve stability, and supporting sustainable development is analyzed. The application advantages and performance indicators of low-dimensional carbon materials compared to other low-dimensional materials in OSC are discussed. Finally, the problems and key research directions in the preparation and new energy application research of coal-based low-dimensional carbon materials were analyzed and summarized. With the continuous development of high-value carbon material preparation technology, the reduction of production costs, and large-scale production, these materials are anticipated to have even broader application prospects in the realm of renewable energy.